Incidence of bacterial infections in chronic kidney disease patients admitted in nephrology unit of Kathmandu Medical College Teaching Hospital - Adhikari, Laxman (Journal of Kathmandu Medical College, 2018)
Background: Infectious diseases are one of the leading causes of morbidity and mortality in chronic kidney disease patients, second only to cardiovascular causes. As the incidence of chronic kidney disease is increasing, the number of deaths due to infectious disease is also increasing. Infectious disease includes infection, bacteremia and sepsis in chronic kidney disease patients. Objective: To assess the incidence of bacterial infections in chronic kidney disease patients. Methodology: A prospective cross-sectional study was done among all chronic kidney disease patients admitted over 6 months in Nephrology Unit of Department of Medicine, Kathmandu Medical College Teaching Hospital. Results: 58 patients were admitted with infectious diseases, out of which 6 patients (10.34%) died during treatment while 1 patient (1.78%) left against medical advice. Infection in patients undergoing dialysis (5D) was much more compared to stage 4 or 5chronic kidney disease patients (58.62% vs. 13.79% vs. 17.24% respectively). 19 patients (32.76%) had pneumonia, 16 patients (27.56%) had Urinary Tract Infection while 12 patients (20.70%) had sepsis. Although sepsis was less prevalent compared to pneumonia/ Urinary Tract Infection, deaths due to sepsis was very high. Conclusion: The incidence of bacterial infections in chronic kidney disease patients is still high despite all the improvements in infection control and dialysis practices, and still lots is left to be done to reduce the morbidity and mortality caused by infections in chronic kidney disease patients.